La enseñanza de la Memoria Histórica desde la Comprensión del Conflicto Armado Colombiano en Estudiantes de Grado Noveno en una Institución Educativa Distrital del Municipio de Soacha-Cundinamarca (2022)
The present research monograph has as its central proposal to investigate the political deas in eleventh graders from district school Paulo Freire in the city of Bogotá. To analyze and recollect such ideas was necessary to apply a qualitative methodology, a survey was developed and applied to recollect the necessary information which help to understand how in several classes a democratic thought is created and promoted that allows students to think and give opinions in a critical, authentic way according to political and social issues, on the other hand, it was possible to know the likes and alternative political scenarios of the students, in the same way, a general discomfort was evidenced promoved by adults subestimation and traditional politics of the country